1998
DOI: 10.1074/jbc.273.6.3747
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Protein Synthesis in Ventricular Myocytes by Vasopressin

Abstract: Protein synthesis in H9c2 ventricular myocytes was subject to rapid inhibition by agents that release Ca 2؉ from the sarcoplasmic/endoplasmic reticulum, including thapsigargin, ionomycin, caffeine, and arginine vasopressin. Inhibitions were attributable to the suppression of translational initiation and were coupled to the mobilization of cell-associated Ca 2؉ and the phosphorylation of eIF2␣. Ionomycin and thapsigargin produced relatively stringent degrees of Ca 2؉ mobilization that produced an endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…8A, treatment of H9c2 cells with vasopressin resulted in a ϳ10 -12-fold increase in GATA-4 protein levels as early as 30 min following exposure to the hormone. The molecular chaperone BiP, a protein whose expression is known to be stimulated following vasopressin-induced hypertrophy (38,39), demonstrated increasing expression, while Cdk1 protein content was inhibited within 1 h of exposure consistent with hypertrophic reprogramming. Northern analysis of steady-state GATA-4 mRNA abundance demonstrated only a ϳ2-fold increase in transcript levels (Fig.…”
Section: Gata-4 Ires Activity Is Stimulated During Vasopressin-inducedmentioning
confidence: 94%
“…8A, treatment of H9c2 cells with vasopressin resulted in a ϳ10 -12-fold increase in GATA-4 protein levels as early as 30 min following exposure to the hormone. The molecular chaperone BiP, a protein whose expression is known to be stimulated following vasopressin-induced hypertrophy (38,39), demonstrated increasing expression, while Cdk1 protein content was inhibited within 1 h of exposure consistent with hypertrophic reprogramming. Northern analysis of steady-state GATA-4 mRNA abundance demonstrated only a ϳ2-fold increase in transcript levels (Fig.…”
Section: Gata-4 Ires Activity Is Stimulated During Vasopressin-inducedmentioning
confidence: 94%
“…H9c2 myoblasts, derived from embryonic rat ventricle, were an excellent model system in which to directly test the effects of V 1A R signaling during in vitro stress, as they express cardiac and skeletal isoforms of L-type Ca 21 channels, sarcolemmal ATPase splice variants characteristic of a normal heart and endogenous V 1A R, which respond to AVP with typical Ga q protein-coupled receptor responses (Hescheler et al, 1991;Sipido and Marban, 1991;Hammes et al, 1994;Tran et al, 1995;Reilly et al, 1998;Chen and Chen, 1999;Guo et al, 2012). During the development of the H/R model, we initially found that H/R increased caspase 3/7 activity and decreased cell viability with enhanced robustness over normoxic conditions only under serum-free conditions, whereas the presence of fetal bovine serum protected the cells.…”
Section: Avp Protects H9c2mentioning
confidence: 99%
“…In the experiments shown in Figs. 5 and 6, [Ca 2ϩ ] i was directly manipulated by preincubation of 293T cells with ionomycin and 3 mM EGTA, followed either by incubation with ionomycin/2 mM Ca 2ϩ or by continued incubation with ionomycin/EGTA, essentially according to the protocol of Reilly et al (41). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, [Ca 2ϩ ] i -dependent phosphorylation of an elongation factor, eEF2 by a Ca 2ϩ /CaM-dependent protein kinase, elongation factor-2 kinase, is thought to reduce the rate of peptide chain elongation to the point where it becomes ratelimiting for overall rates of translation (62)(63)(64). The stimuli capable of mobilizing [Ca 2ϩ ] i and inhibiting translation, such as ionomycin, thapsigargin, or the excitotoxic glutamate receptor agonist N-methyl-D-aspartate (41,(63)(64)(65), evoke cellular stress responses that, if prolonged, lead to cell death, a process that may underly pathological conditions such as transient ischemia or neurodegenerative disease (reviewed in Ref. 66).…”
Section: Discussionmentioning
confidence: 99%